Changing Boundaries: The Policies of Workfare in the U.S. and Europe. Issue 1 (26th March 2013) - Brodkin, Evelyn Z.; Larsen, Flemming
Abstract In recent decades, workfare‐style policies have become part of the institutional architecture of welfare and labor market arrangements around the world. In this article, we offer a comparative, historical view of workfare's advance. Our analysis recognizes the complexity and diversity of what we call the "policies of workfare" and highlights the different paths through which these policies have developed in the U.S. and parts of Europe. We argue that it is necessary to look beyond familiar policy labels and language in order to consider workfare‐style policies as part of a broader political project that is altering the boundary between the democratic welfare state and the market economy. We see workfare policies as boundary‐changing, with potentially profound implications both for individuals disadvantaged by market arrangements and for societies seeking to grapple with the increasing instability and precariousness of work in the "new" economy.